Ibon manual on facilitating participatory research. (Ibon Foundation, 2004)
A manual that wants to take the principles of participatory research to its maximum realization through the people's research, a scientifically conducted participatory research in which the people in the localities where the research is being conducted are the principal actors in designing the research, implementing it and evaluating the result.